대학 창업지원의 영향요인 분석 및 적용: 서울대학교를 중심으로 - 임정묵; 성창수; Lim, Jeongmook; Sung, Chang Soo (벤처창업연구, 2025)
This study investigates the evolving role of universities as central actors in regional startup ecosystems and aims to systematically identify the key determinants of effective university startup support. Drawing on a comprehensive review of national and international startup support policies, entrepreneurship ecosystem literature, and established measurement frameworks, six overarching categories and eighteen sub-factors were derived. These include: policy and institutional framework, human capital, technology, entrepreneurial culture, support programs, and collaboration and infrastructure. A modified Delphi method was employed, involving experts from academia, the private sector, and local government, to validate and refine the identified factors. Subsequently, the framework was applied to a case study of Seoul National University (SNU), a leading research institution undergoing a transition toward an entrepreneurial university model. The findings reveal that SNU actively implements key support mechanisms-such as internal and external funding allocation, and regional cluster development-while also highlighting areas for improvement, including startup-talent matching, expanded access to technical infrastructure for proof-of-concept validation, enhanced alumni networks, and strengthened global support programs. This research contributes to the literature by developing a robust, empirically grounded framework for university startup support. It offers strategic insights for higher education institutions seeking to scale entrepreneurial initiatives and informs policy discourse on fostering innovation-driven university ecosystems. 본 연구는 대학이 지역 창업생태계의 핵심 주체로 부상하는 최근의 흐름에 주목하여, 대학 창업지원의 영향 요인을 체계적으로 도출하고 이를 서울대학교 사례에 적용하여 운영 현황 분석 및 개선 방향을 제시하는 것을 목적으로 한다. 연구 방법으로는 국내·외 창업지원 정책과 창업생태계 관련 선행연구 및 측정지표를 기반으로 주요 요인을 도출한 후, 대학·민간·지자체 창업지원 전문가를 대상으로 델파이 분석을 수행하였다. 분석 결과, 대학 창업지원의 주요 영향요인은 '정책 및 제도', '인력', '기술', '문화', '지원', '협력 및 인프라'의 6개 상위요인과 18개의 하위요인으로 도출되었다. 이를 서울대학교 사례에 적용한 결과, 교비 및 사업비를 활용한 창업지원, 지역 연계 창업클러스터 조성 등 주요 요인이 실질적으로 운영되고 있음을 확인하였다. 또한 창업기업과 인력 간 매칭 활성화, 기술 실증 시 대학 기자재 활용 확대, 동문 창업 네트워크 개선, 글로벌 창업지원 프로그램 강화 등 개선이 요구되는 영역이 확인되었다. 본 연구는 대학 창업지원의 주요 영향요인을 통합적으로 도출하고 실증함으로써, 향후 타 대학의 창업지원 체계 고도화 및 창업생태계 활성화를 위한 전략 수립에 학술적 기초자료로 활용될 수 있다. 아울러 교육과 연구 중심의 전통적 대학에서 기업가적 대학으로 전환을 모색하는 대학창업생태계 조성에 있어 수행해야 할 역할을 구체화하고 정책 및 제도 개선을 위한 실천적 시사점을 제공한다.